2004
DOI: 10.1016/j.jvs.2004.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Aortofemoral bypass in young patients with premature atherosclerosis: is superficial femoral vein superior to Dacron?

Abstract: AFB performed with SFV grafts is a far more durable operation than standard D-AFB in young patients with aortoiliac occlusive disease. However, V-AFB is far more likely to require lower extremity fasciotomy, and takes almost twice as long to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Clagett et al, 1 in a series of 41 patients, emphasized the excellent long-term patency of the FV graft with a cumulative patency rate of 100% at 5 years. Jackson et al, 3 graft to Dacron graft in aortofemoral bypasses in patients younger than 55 years treated for aortoiliac occlusive disease, with a patency rate at 5 years of 100% vs 50%, respectively. On the basis of these results, the authors recommended that use of FV as arterial conduit may be considered in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clagett et al, 1 in a series of 41 patients, emphasized the excellent long-term patency of the FV graft with a cumulative patency rate of 100% at 5 years. Jackson et al, 3 graft to Dacron graft in aortofemoral bypasses in patients younger than 55 years treated for aortoiliac occlusive disease, with a patency rate at 5 years of 100% vs 50%, respectively. On the basis of these results, the authors recommended that use of FV as arterial conduit may be considered in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Use of prosthetic in this patient population has a low primary patency; however, the use of deep vein as conduit results in significantly better 5-year patency rate, with nearly 90% limb salvage. 9 Several factors have been associated with aortobifemoral bypass failures, including young age, virulent aortic disease, small aortic size (such as in women), and progressive infrainguinal disease. 10,11 Patients with these factors have lower primary and secondary patency rates at 5 years, with primary patency rates as low as 66% in patients aged <50 years reported.…”
Section: Discussionmentioning
confidence: 99%
“…hypercoaguable syndrome). Our series used prosthetic graft for all ABF operations, however Jackson and colleagues 27 have demonstrated that autogenous femoral-popliteal vein may be superior in patients with premature atherosclerotic disease(e.g. age <55).…”
Section: Discussionmentioning
confidence: 99%